Problem-based learning with baamboozle edugame: Enhancing critical thinking skills and learning interest - Endang Wahyuningsih; Fina Hanifa Hidayati; Ghufron Zaida Muflih; Fersellia Fersellia (Journal of Advanced Sciences and Mathematics Education, 2024)
Background: Developing students' critical thinking skills and learning interest is essential in mathematics education, particularly in complex topics like discrete mathematics. Problem-Based Learning (PBL) models, integrated with educational technology such as the Baamboozle edugame, have the potential to address these educational challenges.Aim: This study investigates the effect of the Problem-Based Learning (PBL) model assisted by the Baamboozle edugame on students' critical thinking skills and their learning interest.Method: A quasi-experimental design was employed, involving an experimental group using the PBL model with Baamboozle and a control group following conventional teaching methods. Data were collected using posttest instruments to measure critical thinking skills and learning interest.Results: The findings reveal significant differences in both critical thinking skills and learning interest between the experimental and control groups. The experimental group achieved an average posttest score of 84.28 in critical thinking skills compared to 53.43 in the control group. For learning interest, the experimental group scored 75.83, outperforming the control group's 70.13.Conclusion: The study concludes that the PBL model integrated with the Baamboozle edugame effectively enhances students' critical thinking skills and learning interest in discrete mathematics. This approach demonstrates the potential of combining innovative learning models with educational technology to improve student outcomes.